Human resources in the Cape midlands - Truu, Mihkel Lemmit (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1972)
From Preface: Although Alfred Marshall's definition of economics has been criticised for its allegedly narrow conception of the subject, it is sometimes overlooked that he considered the study of wealth but one side of the matter. To Marshall, the other and "more important" side of economics was that it also forms "a part of the study of man". The basic thought which underlies the present study is a similar one, namely, that economics is not only concerned with goods and service, but also with men and human action. It is spatially confined to an analysis of the human resources in a region consisting of 21 magisterial districts in the Eastern Cape Province, which cover an area of 72, 462 square kilometres, collectively described here as the Cape Midlands.
Keywords: Human capital -- South Africa; Personnel management -- South Africa -- Cape of Good Hope